Enhancing Themes and Strengths Assessment: Leveraging Academic-Led Qualitative Inquiry in Community Health Assessment to Uncover Roots of Community Health Inequities. Issue 4 (July 2017) - Hebert-Beirne, Jennifer; Felner, Jennifer K.; Castañeda, Yvette; Cohen, Sheri
Abstract : Context: Rigorous qualitative research can enhance local health departments' efforts to gain a deeper insight into residents' perceived community health inequities necessary for productive community health assessments (CHAs) and community health improvement plans (CHIPs). Objective: The Chicago Department of Public Health and the Partnership for Healthy Chicago used the National Association of County & City Health Officials' Mobilizing for Action through Planning and Partnerships (MAPP) model to conduct its CHA/CHIP, Healthy Chicago 2.0 (HC 2.0). Public health graduate students conducted qualitative research for part of the Community Themes and Strengths Assessment (CTSA), one of the 4 MAPP assessments. Design: Using a health equity lens, this qualitative component included focus groups and oral histories with residents in Chicago Community Areas with the highest social and economic hardship to better understand how residents perceive health inequities in their respective neighborhoods. Settings: Community-based organizations in 6 Chicago neighborhoods with the highest quartile of social and economic hardship. Participants: Forty-eight Chicago residents from 5 community areas participated in focus groups, and 6 residents of a Mexican ethnic enclave shared oral histories. Main Outcome Measure: Residents' perceptions of community needs and assets. Results: Needs identified include inaccessible resources and opportunities, economic instability, and safety. Assets include the efficacy and agency of resilient residents, as well as faith and spirituality. Systemic and institutional discrimination was identified at the roots of community health inequities. Conclusion: Through qualitative inquiry, the more nuanced understanding of how residents perceive health inequities better positioned HC 2.0 to develop upstream strategies in line with advanced health equity practice. Engaging qualitative academic researchers in CTSA brings academic expertise to enrich the CHA while providing real-time learning experiences to prepare future public health practitioners to work on upstream structural determinants of health. Abstract : Supplemental Digital Content is Available in the Text.